The Influence of Rewards, Punishments, and Work Environment on Work Motivation - Prasasti, Andriantri Dian; Armanu (Jurnal Kewirausahaan dan Inovasi, 2025)
The objective of this research is to identify the effects of reward, punishment, and workplace environment on work motivation. This research is categorized as explanatory research, which is used to develop and validate causal relationships between variables through hypothesis testing. Since the population only consists of 100 people, all of them were included as the research sample. They are employees of Roxy Square of Jember with the minimum age of nineteen years. The research data was harvested from paper-based 5-point Likert-scaled questionnaires and was analyzed using multiple linear regression. Instrument test, classical assumption test, and hypothesis testing were conducted. This study finds that reward, punishment, and workplace environment have positive and significant effects on the work motivation. Therefore, this study suggests the company to maintain the application of the reward and punishment system and improve the workplace environment so that the employees can benefit from increased work motivation.